2007
DOI: 10.1371/journal.pone.0001190
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily Conserved Protein Sequences of Influenza A Viruses, Avian and Human, as Vaccine Targets

Abstract: BackgroundInfluenza A viruses generate an extreme genetic diversity through point mutation and gene segment exchange, resulting in many new strains that emerge from the animal reservoirs, among which was the recent highly pathogenic H5N1 virus. This genetic diversity also endows these viruses with a dynamic adaptability to their habitats, one result being the rapid selection of genomic variants that resist the immune responses of infected hosts. With the possibility of an influenza A pandemic, a critical need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(147 citation statements)
references
References 90 publications
5
141
0
1
Order By: Relevance
“…The sampling of internal viral proteins by class I HLA is an elegant complement to humoral responses that target the solvent-accessible epitopes of external viral proteins: In combination, the humoral and cellular components of the adaptive immune system target epitopes from both internal and external viral proteins. The observation that internal viral proteins are more conserved than surface proteins (29) suggests that internal proteins may be more promising immunotherapeutic agents. However, such a conclusion is premature as we cannot predict whether various HLA will interact with influenza in a fashion similar to the common molecule HLA-B*0702.…”
Section: Discussionmentioning
confidence: 99%
“…The sampling of internal viral proteins by class I HLA is an elegant complement to humoral responses that target the solvent-accessible epitopes of external viral proteins: In combination, the humoral and cellular components of the adaptive immune system target epitopes from both internal and external viral proteins. The observation that internal viral proteins are more conserved than surface proteins (29) suggests that internal proteins may be more promising immunotherapeutic agents. However, such a conclusion is premature as we cannot predict whether various HLA will interact with influenza in a fashion similar to the common molecule HLA-B*0702.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the proteins' primary structure of different virus strains showed that 80% of the virus strains of human and avian viruses contain five of eleven proteins (PB2, PB1, PA, NP, and M1) with the homological regions from 9 to 58 amino acids long. It is known that the HA protein has the 9 amino acid region that is a part of the fusion peptide (FGAIAGFIA) and is identical for all the influenza A viruses [65].…”
Section: Volume 3 Number 1 2016mentioning
confidence: 99%
“…3) (Digard et al, 1999;Momose et al, 2001;Ng et al, 2008Ng et al, , 2009Noton et al, 2009;Wang et al, 1997;Ye et al, 2006). Moreover, phylogenetic analysis of viral strains isolated from different hosts revealed that the NP gene is relatively well conserved (Shu et al, 1993), especially in the functional domains (Heiny et al, 2007;Li et al, 2009;Ng et al, 2009). Thus, all of these functional domains could be considered potential targets for antiviral agents.…”
Section: Function Of Npmentioning
confidence: 99%